DAMPAK LINGKUNGAN DAN SOSIAL DARI PENGEMBANGAN CBM DI INDONESIA - Hartiniati, Hartiniati (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2011)
Indonesia has one of the largest Coal Bed Methane (CBM) reserves in the world withÃ‚Â a potential 453 trillion cubic feet (Ã¢â‚¬Å“TcfÃ¢â‚¬Â), more than double the countryÃ¢â‚¬â„¢s natural gasreserves. The government, therefore, is planning to exploite its huge potential reservesÃ‚Â and targetting to produce 1 billion standard cubic fee per day, or about 0.18 million barrelof oil equivalent, by 2025. Several new regulations have been passed, but non is relatedÃ‚Â to protection to the environment as an impact of the development of CBM. If it is notÃ‚Â well regulated and managed properly, the environmental impact will be enormous. ThisÃ‚Â paper presents assessment results on the environmental and social impacts which likelywill be faced by Indonesia from improper development of CBM in Indonesia. Certainly,Ã‚Â there will be very serious and unaviodable negative impacts to the environment withoutcareful plan and proper environmental regulation put in place prior to the developmentÃ‚Â of CBM. The government will have to develop a specific regulation regarding CBMdevelopment in the near future before everything is too late.